Breaking the Chains of ‘Pasung’: The Potential Roles of Primary Health Centres and Pharmacists in an Indonesian Setting - Sulisetiorini Sulisetiorini; Yosi Irawati Wibowo; Bruce Sunderland; Adji Prayitno Setiadi (Journal of Public Health and Pharmacy, 2025)
Introduction: Healthcare for patients in pasung is often neglected. Limited data is available on the roles of Primary Health Centres (PHCs) as the main providers of primary care in Indonesia. This research aims to explore health services provided for patients in pasung at PHCs and to identify the roles of pharmacists. Methods: This descriptive qualitative research used in-depth interviews with a range of stakeholders [i.e., patients in pasung (n=14) or the representative family caregivers (n=12), mental health nurses (n=5), pharmacists (n=5)] at 5 PHCs in Trenggalek, Indonesia from May to July 2023. Inductive thematic analysis was used to address the research questions. Ethical approval was obtained from the Research Ethics Committee of Universitas Surabaya (number 130/KE/V/2023), and participants provided written informed consent. Results: Patients in pasung have generally had adequate access to PHCs with no charge for their treatments. Health services provided for patients in pasung at PHCs were categorised into two main themes: outpatient services (i.e., medication supply, and home-care), and referral to inpatient services. Pharmacists’ roles have largely related to drug supply, while clinical pharmacy services have been very limited (e.g., providing drug information when patients obtained their medications at the pharmacy units). Conclusion: In conclusion, findings in this study have provided a baseline for future development of mental healthcare for patients in pasung. Pharmacists have the potential to take up more clinical roles to ensure quality use of medicines among patients in pasung. Supporting policy and resources should be allocated for PHCs to expand pharmacist’s services.